Beyond discomfort? Equity coaching to disrupt whiteness. Issue 2 (3rd July 2018) - Blaisdell, Benjamin
ABSTRACT: White discourse is a discourse that functions to support white supremacy. Based on an ethnographic study in a U.S. elementary school, this article analyses how white teachers use appeals to discomfort as a form of white discourse to resist school-based racial equity work. It also examines how equity coaching – an approach to professional development rooted in critical race theory – can be used to augment the voices of teachers of colour, reframe narratives of discomfort, and disrupt the power of white discourse.